ANTISIPASI DIDAKTIS DENGAN ALAT PERAGA UNTUK MENGATASI HAMBATAN EPISTEMOLOGI DALAM MATERI PERPANGKATAN KELAS IX MTS - Damayanti, Uli; Sugiatno, Sugiatno; Fitriawan, Dona (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2024)
This study aimed to determine whether didactic anticipation with teaching aids could overcome students' epistemological obstacles in exponential material at Grade IX MTs Islamiyah Pontianak. The research method used in this research is Didactical Design Research (DDR) with a qualitative approach. The data source for this research comprised Grade IX students, and the data included the answer sheets from the pre-test, post-test, and the results of the interviews. The research subjects were three individuals selected using the purposive sampling technique. The results of the study show the epistemological obstacles encountered by the research subjects prior to the didactic anticipation treatment with props, including conceptual obstacles, procedural obstacles, and operational technique obstacles. The didactic anticipation designed to mitigate these obstacles comprises the didactic situation, assignment, expected response, possible difficulties, and anticipation. In anticipation of students' difficulties, teaching aids are employed, namely squares, cubes, paper, and PLAKAT. Changes in epistemological barriers after didactic anticipatory treatment showed that the epistemological barriers experienced by the subjects were reduced. This can be seen from the percentage of reduction in conceptual, procedural, and operational technical obstacles of 77.78%, 50%, and 25%, respectively. Based on the analysis of the changes that occurred, it can be concluded that didactic anticipation with teaching aids can overcome most of the epistemological obstacles of students in grade IX exponential materials.